Impact of Power Transformer Insulating Mineral Oil Degradation on FRA Polar Plot - Aljohani, O.; Abu-Siada, Ahmed (IEEE, 2015)
Frequency response analysis (FRA) has been employed as an effective tool for the detection of various mechanical winding and core deformations within electrical power transformer. Traditional FRA signature interpretation relies on the magnitude of the FRA plot although all practical frequency response analyzers are able to provide both magnitude and angle of the FRA signal in wide frequency range. Moreover, no attention has been given to the impact of power transformer insulating oil degradation on the FRA signature. This paper presents is aimed at introducing a new interpretation approach of the FRA signature using polar plot which is obtained by incorporating FRA signature magnitude and phase into one plot. The paper also investigates the impact of insulating mineral oil degradation on the proposed polar plot signature. Digital image processing (DIP) technique is developed to automate the interpretation process. In this regard, the physical geometrical dimension of a single-phase transformer filled with insulating mineral oil is simulated using three-dimensional finite element analysis to emulate real transformer operation. FRA polar plot signatures are measured and analyzed for various health conditions of the mineral oil. Results show that insulating mineral oil degradation has an impact on the transformer FRA polar plot signature. The proposed FRA polar plot technique is easy to implement within any frequency response analyzer.